Beyond usage: understanding the use of electronic journals on the basis of information activity analysis. Electronic journals, Use studies, Information activity, Scientific communication - Annaïg Mahé (Information Research: An International Electronic Journal)
In this article, which reports the second part of a two-part study of the use of electronic journals by researchers in two French research institutions, we attempt to explain the integration of the use of electronic journals in the scientists' information habits, going beyond usage analysis. First, we describe how the development of electronic journals use follows a three-phase innovation process - research-development, first uses, and technical acculturation. Then, we attempt to find more significant explanatory factors, and emphasis is placed on the wider context of information activity. Three main information activity types are outlined - marginal, parallel, and integrated. Each of these types corresponds to a particular attitude towards scientific information and to different levels of electronic journal use.